PREDADORES DE Didemnum psammatodes (SLUITER, 1895) (CHORDATA: TUNICATA) OBSERVADOS NA PRAIA DO PARAÍSO, CABO DE SANTO AGOSTINHO –PE. - Ferreira, G. F. A.; Almeida, S. M.; Torres, Y. T. P. (Revista Nordestina de Zoologia, 2015)
Ascidians are commonly found in the intertidal zone as fouling communities. They are aggressive competitors for space and live in a restricted hard substrate which is a limiting resource. Didemnidae species are known for their competitive ability of overgrowing and covering other organisms. In this ecosystem, predators play important role in controlling their prey growth. The aim of our study was to identify potential predators of Didemnum psammatodes in Paraíso Beach, Cabo de Santo Agostinho, Pernambuco, Brazil. We took photos of the specimens alive and also of samples on a rocky-shore, which were under pebbles. Subsequently, we carried the samples to the laboratory for identification. We found two species preying D. psammatodes colonies: the flatworm Thysanozoon brocchi and the gastropoda Lamellaria mopsicolor. Both are well known in the literature for active predation upon ascidians. This was the first record of these species and their predation-prey interaction with D. psammatodes in Pernambuco coast.